2004
DOI: 10.1103/physreve.69.061711
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between surface order and surface azimuthal anchoring strength of nematic liquid crystals

Abstract: The liquid-crystal molecular order near the rubbed polymer surface is reexamined by the improved torque balance method. The surface azimuthal anchoring strength measured by the improved torque balance method is several times larger than that believed conventionally, considered to be significantly affected by the phase-transition behavior. Based on this result, it can be argued that the correlation between the rubbing strength and the surface azimuthal anchoring strength should be improved in consideration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Turning to the factors W ϕ 2 and C int separately, there is ample evidence from the literature that W ϕ 2 is not strongly sensitive to rubbing strength. Oka et al [17] observed a sharp increase in W ϕ 2 for very weak rubbing (corresponding to n f approximately onetenth of the smallest nonzero value used in our experiment), above which W ϕ 2 is almost constant with increasing rubbing strength. Likewise, using an atomic force microscope to scribe a polymer alignment layer, Rastegar et al showed that W ϕ 2 is nearly independent of the vertical scribing force for fixed line separation [18].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Turning to the factors W ϕ 2 and C int separately, there is ample evidence from the literature that W ϕ 2 is not strongly sensitive to rubbing strength. Oka et al [17] observed a sharp increase in W ϕ 2 for very weak rubbing (corresponding to n f approximately onetenth of the smallest nonzero value used in our experiment), above which W ϕ 2 is almost constant with increasing rubbing strength. Likewise, using an atomic force microscope to scribe a polymer alignment layer, Rastegar et al showed that W ϕ 2 is nearly independent of the vertical scribing force for fixed line separation [18].…”
Section: Discussionsupporting
confidence: 44%
“…The low n f saturation of W ϕ 2 (Ref. [17]) suggests that the polymer's orientational order parameter at the surface saturates for weak rubbing. But Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the interfacial layer dominates LC anchoring and, because anchoring is closely related with display defects, also with light leakage and image sticking . To reduce image sticking in in‐plane switching (IPS) LCDs, increasing order parameter at the interface and azimuthal anchoring strength is very effective .…”
Section: Parameters That Define Lc Configurationmentioning
confidence: 99%
“…The former is a surface-transition-type (high nematic wettability) LC, the latter is a bulk-transition-type (relatively low wettability) LC. 4) Azimuthal anchoring energy was measured by the torque balance method. 5) The deviation angle ÁÈ from the ridge of the gratings indicates the azimuthal anchoring energy A caused by the relief grating.…”
mentioning
confidence: 99%